NUMERICAL STUDY OF THE ERYTHRITOL MELTING PROCESS IN A TRIDIMENSIONAL RECTANGULAR CAVITY - Raymundo, J. F.; Borahel, R. da S.; Oliveski, R. de C. (Revista de Engenharia Térmica, 2015)
Many areas of engineering, such as the petrochemical and food industries, use thermal energy storage to achieve better performance. Thermal energy storage can be used as a heat source or a heat sink. The thermal storage/release technology, based on the use of phase change materials (PCMs), which possess a great capacity of heat accumulation, has raised an important practical interest. Indeed, the improved storage density and the constant temperature release of energy allow a more compact heat exchange design and simplify system management. Phase change phenomena occurring during PCM melting and PCM solidification need to be carefully controlled. The aim of the present numerical study is to investigate the heat transfer and hydrodynamic characteristics of a phase change material (PCM) in a rectangular cavity and the melting process dependence on the cavity height. The geometry consists of a mini rectangular cavity which contains PCM. Water or steam flows in the longitudinal direction of the cavity, thus heating or cooling the PCM in the cavity. The computational domain is made of three materials: air, aluminum and PCM. The grid mesh is structured, hexaedrical and refined near the walls. The study is developed with different operation conditions of the mass flow and water temperature. The numerical simulation is developed through CFD (Computational Fluid Dynamics) with the Fluent code. The mathematical model was validated using results available in the literature. Results of temperature, velocity and volume fraction fields indicate that the cavity height has no impact on the melting process.